Produktion of Shallot (Allium cepa L.) Crops on Various Fertilizer Do Sage Levels - Ali, Akhmad; Sangadji, Ismail; Soekamto, Mira Herwati (Agrikan Jurnal Agribisnis Perikanan, 2024)
Shallots are a flavor and aroma enhancer, one of the leading vegetable crop commodities that farmers have been cultivating intensively for a long time. This is because shallots have quite high economic value. Even though farmers' interest in shallots is quite strong, various obstacles are still encountered in the business process, both technical and economic (Sumarni and Hidayat, 2015). Red onion consumption in Indonesia is 4.56 kg/capita per year or 0.38 kg/capita per month, so national consumption is estimated to reach 1,608,000 tons per year (Directorate General of Horticulture, 2017). This proves that the availability of shallots in the country is not sufficient for the high demand of consumers, thus shallot productivity needs to be increased further. One of the factors that influences national shallot production is the condition of the soil which lacks nutrients due to continuous use by farmers. Efforts are needed to apply appropriate technology to increase shallot production yields. One technology that can be applied in cultivating shallot plants due to soil lacking nutrients is fertilization. The results show the fertilizer dosage treatment. Where this dosage level produces the best growth components (plant height and number of leaves) and production components (wet stover weight and dry stover weight) for shallot plants.